ADAPTIVE LEADERSHIP IN TIMES OF GLOBAL CRISIS: CASE STUDIES FROM THE COVID-19 PANDEMIC - Febriawan Ardi Nugroho (Yayasan Adra Karima Hubbi, 2025)
The COVID-19 pandemic has posed unprecedented challenges globally, necessitating a reevaluation of leadership strategies. Adaptive leadership, characterized by flexibility and responsiveness, has emerged as a crucial approach for navigating crises. This research aims to investigate the role of adaptive leadership during the COVID-19 pandemic, focusing on how leaders adjusted their strategies to manage uncertainty and foster resilience within their organizations. A qualitative case study methodology was employed, involving in-depth interviews with leaders from various sectors affected by the pandemic. Data was collected to explore the decision-making processes, communication strategies, and adaptive measures implemented to address the crisis. The analysis revealed key themes related to transparency, collaboration, and emotional intelligence as essential components of effective adaptive leadership. Findings indicate that leaders who embraced adaptive leadership principles were better equipped to navigate the complexities of the pandemic. They demonstrated agility in responding to rapidly changing circumstances, fostering a culture of trust and open communication. Additionally, these leaders prioritized employee well-being, which contributed to higher levels of engagement and morale during challenging times. In conclusion, the study underscores the importance of adaptive leadership in crisis situations. It highlights the need for leaders to develop the skills necessary for flexibility and responsiveness to effectively manage future global crises. The insights gained from this research can inform leadership development programs and provide valuable lessons for organizations facing similar challenges in the future.